2005
DOI: 10.1088/0029-5515/45/8/025
|View full text |Cite
|
Sign up to set email alerts
|

Temperature gradient driven electron transport in NSTX and Tore Supra

Abstract: Electron thermal fluxes are derived from the power balance for Tore Supra (TS) and NSTX discharges with centrally deposited fast wave electron heating. Measurements of the electron temperature and density profiles, combined with ray tracing computations of the power absorption profiles, allow detailed interpretation of the thermal flux versus temperature gradient. Evidence supporting the occurrence of electron temperature gradient turbulent transport in the two confinement devices is found. With control of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…26 The electrostatic potential in the saturated state is plotted in Fig. 13 for r/a=0.55, and the formation of streamer-like structures with a radial extent of up to 200ρ e (∼ 2 cm) is clearly seen.…”
Section: Theory Calculations and Turbulence Measurementsmentioning
confidence: 97%
“…26 The electrostatic potential in the saturated state is plotted in Fig. 13 for r/a=0.55, and the formation of streamer-like structures with a radial extent of up to 200ρ e (∼ 2 cm) is clearly seen.…”
Section: Theory Calculations and Turbulence Measurementsmentioning
confidence: 97%
“…Understanding electron thermal transport and the causes giving rise to the anomalous levels experimentally observed is a key requirement in order to achieve a predictive capability for the confinement of future fusion devices such as ITER or FNSF (Fusion Nuclear Science Facility). 4 Ample theory and numerical simulations [5][6][7][8][9][10][11][12] have suggested that micro instabilities driven by the electron temperature gradient (ETG) could be responsible for anomalous electron thermal transport levels observed experimentally. The ETG toroidal instability has a characteristic scale length on the order of the electron gyro radius (k ?…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the low toroidal field leads to a large electron gyroradius which facilitates measuring turbulence wavenumber spectrum. Indeed, in a previous study an electromagnetic ETG transport model has been applied to an NSTX RF-heated L mode plasma and good agreement with measurements have been found [12], although there was no measurement of electron-scale turbulence. In order to make direct measurements, a novel 280 GHz microwave scattering system (the high-k scattering system) was implemented on NSTX [13], and this diagnostic has provided first experimental evidence of ETG turbulence in NSTX RF-heated L mode plasmas [14]: It was found that measured electron-scale turbulence is driven by the electron temperature gradient, and the observed critical gradient for linear instability is shown to be consistent with linear gyro-kinetic calculations for the ETG mode.…”
Section: Introductionmentioning
confidence: 93%